Critical Pedagogy Trends in English Language Teaching - Portilla Quintero, Brenda; Herrera Molina , Jennifer (Colombian Applied Linguistics Journal, 2021)
This article presents a literature review regarding the latest trends in the inclusion of Critical Pedagogy (CP) in English Language Teaching (ELT) in different countries worldwide and in Colombia, considering its different regions. A review of different articles was conducted by considering four databases that include two regional and two international journal directories in both English and Spanish. The papers were analyzed and discussed from a mixed approach in which four keywords were tracked, and factors such as geographical distribution, as well as the way in which CP was implemented in the studies, were identified. The results of this query show that CP in ELT is an emerging trend, especially in countries where political, social, and economic inequality remains. In the same way, the findings suggest that different strategies regarding curricula analysis, the role of teachers and students as social subjects, among others, have been carried out in order to foster the understanding of this theory and its application and considerations in real-life contexts. Attempts to implement CP in English classes have proven to be meaningful experiences and constructive at developing critical thinking strategies in students.